2019
DOI: 10.1021/acs.jpclett.9b02751
|View full text |Cite
|
Sign up to set email alerts
|

Fine Modulation of the Higher-Order Excitonic States toward More Efficient Conversion from Upper-Level Triplet to Singlet

Abstract: Hot exciton luminogens capable of harvesting nonemissive triplet excitons via reverse intersystem crossing from high-order triplet (hRISC) to singlet have great potential in high-efficiency fluorescent organic light-emitting diodes (OLEDs). Although spin–orbit coupling (SOC) is regarded as a key factor affecting the RISC process, its effects on hot exciton materials are poorly understood. Herein, we design and synthesize two blue-emitting hot exciton luminogens, PABP and PAIDO, to study this issue by modulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 33 publications
(45 reference statements)
0
57
0
Order By: Relevance
“…It was found that all three compounds present low energy levels of T 1 and clearly large energy gaps between T 2 and T 1 (ΔE T2-T1 ), which can greatly suppress interconversion (IC) decay from T 2 to T 1 as the rate of IC is in an inverse relation with ΔE T2-T1 . 36 In contrast, the three compounds exhibit small energy gaps between T 2 and S 1 , which can trigger spin-flip at high-lying excited states and boost the high-lying reverse intersystem crossing (hRISC) process occurring from T 2 to S 1 , according to the Fermi golden rule. [37][38][39] Moreover, the three compounds exhibit large spin-orbital coupling (SOC) constants between T 2 and S 1 states (<S 1 |Ĥ SO |T 2 >, Supporting Information Table S1), which are in favor of fast hRISC.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…It was found that all three compounds present low energy levels of T 1 and clearly large energy gaps between T 2 and T 1 (ΔE T2-T1 ), which can greatly suppress interconversion (IC) decay from T 2 to T 1 as the rate of IC is in an inverse relation with ΔE T2-T1 . 36 In contrast, the three compounds exhibit small energy gaps between T 2 and S 1 , which can trigger spin-flip at high-lying excited states and boost the high-lying reverse intersystem crossing (hRISC) process occurring from T 2 to S 1 , according to the Fermi golden rule. [37][38][39] Moreover, the three compounds exhibit large spin-orbital coupling (SOC) constants between T 2 and S 1 states (<S 1 |Ĥ SO |T 2 >, Supporting Information Table S1), which are in favor of fast hRISC.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Hence, the RISC is likely owed to the T 1 state via an intermediary T n (n ≥ 2) with large SOC and small energy differences (Table S2, Supporting Information), as proposed for some other emitters. [ 41–43 ] Furthermore, based on Φ F and fluorescence lifetimes of the doped films, the main kinetic parameters are calculated and tabulated in Table S3, Supporting Information. The radiative rate constants ( k r ) of the QA‐Ns calculated from the prompt PL quantum efficiency (Φ PF ) and τ P are larger than those of other flexible emitters, which indicates the effective radiative transition process owing to the high oscillator strengths and large conjugated rigid molecular frameworks.…”
Section: Figurementioning
confidence: 99%
“…Recent experimental studies and quantum chemical calculations ensure that ISC and rISC between 1 CT singlet and 3 LE triplet states are mediated by vibronic coupling of the 3 CT to the locally excited triplet ( 3 LE) states to allow SOC to the 1 CT state, [ 6 ] which accelerates the rate constant of rISC ( k rISC ). [ 7 ]…”
Section: Introductionmentioning
confidence: 99%